Predictors of mortality among initially stable adult pelvic trauma patients in the US: Data analysis from the National Trauma Data Bank. Issue 11 (November 2015) - Wang, Hao; Phillips, J. Laureano; Robinson, Richard D.; Duane, Therese M.; Buca, Stefan; Campbell-Furtick, Mackenzie B.; Jennings, Adam; Miller, Tyler; Zenarosa, Nestor R.; Delaney, Kathleen A.
Abstract: Objectives: Pelvic fractures are associated with increased risk of death among trauma patients. Studies show independent risks predicting mortality among patients with pelvic fractures vary across different geographic regions. This study analyses national data to determine predictors of mortality in initially stable adult pelvic trauma patients in the US. Methods: This study is a retrospective analysis of the US National Trauma Data Bank from January 2003 to December 2010 among trauma patients ≥18 years of age with pelvic fractures (including acetabulum). Over 150 variables were reviewed and analysed. The primary outcome was all-cause in-hospital mortality. Logistic regression analysis was used to determine independent risk factors predictive of in-hospital mortality in stable pelvic fracture patients. Results: 30, 800 patients were included in the final analysis. Overall in-hospital mortality rate was 2.7%. Mortality increased twofold in middle aged patients (age 55–70), and increased nearly fourfold in patients with advanced age ≥70. We found patients with advanced age, higher severity of injury, Glasgow Coma Scale (GCS) <8, GCS between 9 and 12, prolonged mechanical ventilation, and/or in-hospital blood product administration experienced higher mortality. Patients transported to level 1 or level 2 trauma centres experienced lower mortality while concomitantly experiencing higher associated internal injuries. Conclusions: Geriatric and middle aged pelvic fracture patients experience higher mortality. Predictors of mortality in initially stable pelvic fracture patients are advanced age, injury severity, mental status, prolonged mechanical ventilation, and/or in-hospital blood product administration. These patients might benefit from transport to local level 1 or level 2 trauma centres.